Development of True Shallot Seed Technology as an Effort to Increase Red Onion (Allium Cepa L.) Production in Galung Lombok Village, Polewali Mandar, West Sulawesi - Arham, Ihsan; Kasim, Niken Nur; Zainuddin, Dian Utami (Pascasarjana Universitas Mataram, 2024)
This community service aims to improve the capacity of shallot farmers in Galung Village, Lombok, Polewali Mandar, in implementing True Shallot Seed (TSS) technology as an effort to increase shallot (Allium cepa L.) production. The use of TSS is an innovation that can increase harvest yields and reduce the risk of disease spread, which is often carried by conventional bulbs. The activity method includes focus group discussions (FGD) to understand participant readiness, preparation of extension materials, and implementation of extension that includes an introduction to the TSS method and comparison with traditional cultivation techniques. Evaluation was carried out with a pre-test and post-test to assess the increase in participant understanding. The evaluation results showed an increase in the average score from 41.63 in the pre-test to 76.08 in the post-test, reflecting an increase in understanding of 82.75%. Further analysis showed that age and farming experience factors did not significantly affect the increase in participant understanding. In conclusion, this program has succeeded in increasing farmer knowledge in TSS-based shallot cultivation techniques, which have the potential to support the sustainability of shallot production and strengthen farmers' economic resilience in the future. It is hoped that the TSS method can be applied more widely through the demonstration plot system to increase farmer confidence in adopting this technology